Efficacy of spectroscopy in oral cancer detection: systematic review - Pavithran, Pinky; Sukumaran, Gheena (Journal of Stomatology, 2024)
The aim of this review was to explore the implementation of spectroscopy in the realm of oral cancer diagnosis. This study was registered in the International Prospective Register of Systematic Reviews database (CRD42023405597). A thorough examination of the existing body of literature was conducted using electronic databases, such as Cochrane Library, PubMed, Scopus, NLM, and Web of Science, without language limitation. The search encompassed articles published from the year 2000 onwards. The main outcome was the analysis of different spectroscopic techniques used in screening and diagnosis of oral cancer, and its efficacy when used with different sample types. Spectral cytopathology specimens as well as saliva and serum samples were utilized, and demonstrated their effectiveness as diagnostic techniques. Specifically, when examining cytoplasm, healthy donors displayed pronounced protein (636, 845, 997, 1237, 1361, 1597, and 1645 cm–1), while patient samples presented prominent nucleic acid- (721, 780, and 1180 cm–1) and lipid- (1060, 1135, 1300, 1417, and 1745 cm–1) derived bands. Regarding in vivo detection of oral squamous cell carcinoma (OSCC) in tumor and healthy tissues from surgical resection, cytology specimens showed prominent protein (741, 740, and 1140 cm–1, and 1060 cm–1, respectively), and saliva samples presented pronounced lipid (1437 cm–1). These findings provide valuable insight into variations between healthy individuals and those with potentially malignant lesions using spectra.